DETERMINANTS AND LEVEL OF SMALLHOLDERS’ ANCHOTE MARKET PARTICIPATION IN GIMBI DISTRICT OF SOUTHWESTERN ETHIOPIA: HECKMAN TWO STAGE ANALYSIS - Terefe Negasa; Amsalu Mitiku; Yadeta Bekele Bekere (Agricultural Socio-Economics Journal, 2020)
Anchote is one of the root crops grown in southwestern parts of Ethiopia. Even though market participation has got a due attention by government, smallholder farmers’ participation in fair market is still below the requirements. This study aims to identify determinants of smallholder anchote farmers’ market participation decision and their level of participation. Both primary and secondary data were collected from 162 randomly selected anchote farmers.  Descriptive statistics and heckman two stage models were used to analyze the data. The econometric model result revealed that decision of anchote market participation were significantly determined by quantity of anchote produced, access to extension service, age of household head, ownership of transportation facilities and lagged price. On the other hand, the extent of anchote market participation were significantly determined by sex of household head, quantity of anchote produced, access to market information, income from other crops and family size. Therefore, enhancing farmers’ access to market information, boosting the production and productivity of anchote through better extension services and infrastructures, awareness creation on gender balanced market engagement and improvement in transportation facilities are the critical points that should get policy attentions in the study area.